Influence of extraction methods on total phenolic content and antioxidant properties of some of the commonly used plants in Thailand - Noppawat Pengkumsri (2019)
© 2019 Noppawat Pengkumsri et al. Background and Objective: Several plants have been commonly used in Thailand for health improvement, but the phytochemical content and its bio-activities are not yet elucidated completely. The aim of this research was to study the influence of extraction method on total phenolic content (TPC) and antioxidant activity of representative plants such as Punica granatum, Hibiscus sabdariffa, Cleistocalyx operculatus (Roxb.) Merr., Clitoria ternatea Linn., Mulberry and Oryza sativa L. indica. Methodology: The samples were subjected to different extraction procedures. The TPC and phenolic compounds were determined by Folin-Ciocalteu colorimetric assay and HPLC, respectively. The antioxidant capacity of the extracts was measured by 2, 2-azino-bis-3-ethylbenzothiazoline-6-sulphonic acid (ABTS) and ferric reducing antioxidant power (FRAP) assays and ferrous ion (Fe2+) chelating assay. Results: The maximum TPC was observed in pomegranate peel (TTP) extract (0.1 M HCl: Ethanol extraction) and low TPC was recorded in aqueous extract of butterfly pea flower (BP) samples. The high content of protocatechuic, p-hydroxybenzoic acid were observed in pomegranate seed and seed coat (TTS). Gallic and syringic acids were found to be rich in pomegranate peel (TTP) and flower of butterfly pea (BP), respectively. Roselle flower samples (KJ) showed high content of chlorogenic, p-coumaric and caffeic acids. Conclusion: The maximum antioxidant activity was observed in extracts obtained by 0.1 M HCl: Ethanol extraction methods, especially pomegranate peel exhibited high free radical scavenging activity compared to that of the other samples. The results strongly revealed that the extraction method greatly influences the phytochemical content and bioactivity and strongly recommends that any plant samples, intended to study, must undergo several extraction processes to reveal the actual phytochemical content.